An unusual cause of acute abdomen: Mesenteric heterotopic pancreatitis causing confusion in clinical diagnosis - Hakan CANBAZ,; Tahsin ÇOLAK,; Duygu DÜŞMEZ APA,; Orhan SEZGİN,; Süha AYDIN, (Turkish Journal of Gastroenterology, 2019)
-